2018
DOI: 10.1038/s41467-018-05418-8
|View full text |Cite
|
Sign up to set email alerts
|

A novel environment-evoked transcriptional signature predicts reactivity in single dentate granule neurons

Abstract: Activity-induced remodeling of neuronal circuits is critical for memory formation. This process relies in part on transcription, but neither the rate of activity nor baseline transcription is equal across neuronal cell types. In this study, we isolated mouse hippocampal populations with different activity levels and used single nucleus RNA-seq to compare their transcriptional responses to activation. One hour after novel environment exposure, sparsely active dentate granule (DG) neurons had a much stronger tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
93
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(101 citation statements)
references
References 82 publications
6
93
1
1
Order By: Relevance
“…Single cell RNA-seq on hippocampal dentate granule cells from mice subjected to novel environments shows differences in transcriptomes between sparsley firing neurons in the dentate gyrus versus quiet cells [19]. When profiles are sorted based on FOS expression, MAGIC was able to call FOS as the second most likely driver of gene changes, placing the highly homologous protein FOSL2 as top rank [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Single cell RNA-seq on hippocampal dentate granule cells from mice subjected to novel environments shows differences in transcriptomes between sparsley firing neurons in the dentate gyrus versus quiet cells [19]. When profiles are sorted based on FOS expression, MAGIC was able to call FOS as the second most likely driver of gene changes, placing the highly homologous protein FOSL2 as top rank [41].…”
Section: Discussionmentioning
confidence: 99%
“…Single cell transcriptome profiling allows the discerning of responses of individual cells to stimuli. Jaeger et al performed single cell profiling on mouse dentate granule cells in response to a novel location stimulus [19]. Cells were sorted on Fos expression, an Immediate Early Gene (IEG) that is expressed in response to neuronal firing [25].…”
Section: ) Tcga(lum_vs_basal) 233 Luminal-a and 79mentioning
confidence: 99%
“…Which aspects of ENR and the mechanisms how environmental stimulation prevents age-related DNA methylation changes remains to be investigated. Previous work has shown that exploration of novel environments leads to neuronal activation coupled with short-term and long-lasting changes in transcription and chromatin accessibility in activated hippocampal neurons 55, 56 . Additionally, isolated neuronal activation by electroconvulsive stimulation has been shown to lead to widespread changes in DNA methylation, RNA and open chromatin landscapes in the dentate gyrus 16, 35 .…”
Section: Discussionmentioning
confidence: 99%
“…To test this notion, DGCs, activated by a 15 min exposure to a novel environment, were isolated 60 min later for single-nucleus genome-wide bisulfite sequencing (snRRBS). PROX + DGC nuclei, expressing the IEG protein FOS, a proxy for neuronal activity, were sorted from PROX + /FOScells from dissected dorsal hippocampi by FACS 28,42 (Fig. 5a).…”
Section: Mainmentioning
confidence: 99%